Bio-organic approach for monitoring the Plant growth for Sustainable agriculture - Narula, Gita Batra; Soni, Kiran; Vadakan, Alka B; Sharma, Shweta; Notnani, Prerna; Ghai, Nancy; Gandhi, Kanika (Future Science, 2023)
Agriculture plays a critical role in sustaining life and driving the economy of India. The idea of sustainable agriculture is a holistic approach to meet the demands of food supply while protecting our environment. Through various sources, it has been found out that the country is running out of the main reservoirs of water to irrigate the fields. The present study investigated the possibility to prepare different natural hydrogels using Chia seeds, Flax seed, Gond katira, Arrowroot powder, Tapioca, Agar-agar, Corn starch, Gelatin, Aloe vera, and their comparison with a synthetic hydrogel used in sanitary napkins. On successful formation of natural hydrogels and getting valuable results in their water holding capacity, the work continued to test their potential on growth and development of seeds of two plants: Moong beans (Vigna radiata) and Fenugreek (Trigonella sp.) along with bio-organic fertilizers prepared from onion, garlic and banana respectively. Seeds were sown in soil less media (Coco-coir) and the study of various parameters like phytotoxicity test, seed germination, water consumption, number of leaves, root and shoot length indicated promising results in the establishment and healthy growth of the seedlings. Use of natural biodegradable hydrogels therefore may prove as an easy, low cost and eco-friendly way to establish the seedling development and subsequent productivity at the commercial level under conditions of water scarcity for sustainable agriculture.